Ehrlichia chaffeensis TRP120 ubiquitinates tumor suppressor APC to modulate Hippo and Wnt signaling - Byerly, Caitlan D.; Zhu, Bing; Warwick, Paityn A.; Patterson, LaNisha L.; Pittner, Nicholas A.; McBride, Jere W. (Frontiers in Cell and Developmental Biology, 2024)
Ehrlichia chaffeensis TRP120 is a multifunctional effector that acts as a ligand mimic to activate evolutionary conserved eukaryotic signaling pathways Notch, Wnt, Hedgehog and Hippo. In addition, TRP120 is also a HECT E3 ubiquitin ligase known to ubiquitinate several host cell regulatory proteins (FBW7, PCGF5 and ENO-1) for degradation. We previously determined that TRP120 ubiquitinates the Notch negative regulator, FBW7, to maintain Notch signaling and promote infection. In this study, we investigated a potential mechanism used by E. chaffeensis to maintain Hippo and Wnt signaling by ubiquitinating the tumor suppressor, adenomatous polyposis coli (APC), a negative regulator of Wnt and Hippo signaling. We determined that APC was rapidly degraded during E. chaffeensis infection despite increased APC transcription. Moreover, RNAi knockdown of APC significantly increased E. chaffeensis infection and coincided with increased active Yap and β-catenin in the nucleus. We observed strong nuclear colocalization between TRP120 and APC in E. chaffeensis-infected THP-1 cells and after ectopic expression of TRP120 in HeLa cells. Additionally, TRP120 interacted with both APC full length and truncated isoforms via co-immunoprecipitation. Further, TRP120 ubiquitination of APC was demonstrated in vitro and confirmed by ectopic expression of a TRP120 HECT Ub ligase catalytic site mutant. This study identifies APC as a TRP120 HECT E3 Ub ligase substrate and demonstrates that TRP120 ligase activity promotes ehrlichial infection by degrading tumor suppressor APC to positively regulate Hippo and Wnt signaling.